Pre-Service English Teachers Ponder Over Asking Referential Questions to Increase Student Talking Time - Koşar, Gülten Koşar (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Teacher talk could be maintained to be a pivotal component of language classroom discourse. Language learner learning is substantially contingent upon teacher talk in that it can be regarded to be a valuable and reliable source of input for students. Teacher questions constitute a considerable proportion of teacher talk, and thus, could impinge upon student talking time. Encouraged by the lack of research into exploring the impact of using referential questions on student talking time and pre-service English teachers’ viewpoints on the functions of teacher talk, what student talk indicates, and what to do to increase student talking time, the researcher decided to conduct this research. The data was gathered from the audio recordings of the lessons taught by two Turkish pre-service teachers of English, post-lesson and end-of-the-study meetings, and field notes. The findings indicated asking referential questions helped increase student talking time. Moreover, the participants believed teacher talk performed various pedagogical functions and student talk carried many positive implications. The participants also offered suggestions for increasing student talking time while decreasing teacher talking time.